Increasing crop production benefits to small producers in Bangladesh - Bryan, Elizabeth; Bell, Andrew Reid; Ringler, Claudia; Ahmed, Akhter (2018)
This paper examined the benefits of key crop production decisions for rural livelihoods across Bangladesh in order to suggest ways in which producers can increase returns to crop production. The study used plot-level data from a household survey to estimate the relative contribution of various inputs and practices to the total value of production from a given plot over the course of one year.